«Tradición retórica en las vidas de Antonio Palomino: esquemas biográficos y extravagancia del artista en El Parnaso español pintoresco y laureado (1724)» - Sánchez Jiménez, Antonio (My University, 2020)
abStRact: This article explores the genre underpinnings of Palomino’s Parnaso by examining the origins of the model in artistic biographies prior to Vasari’s. In particular, we propose that Palomino’s biographies follow patterns and rhetorical topoi akin to those studied by Ernst Kris and Otto Kurz (1987), although Palomino does not take them only from the artistic biography genre, but form a related pattern: the life of the poet. This model determines Palomino’s biographies, in which he introduces, be it via Vasari or under his own steam, certain variants that are very important to understand his way of thinking. Among the traits that Palomino’s Parnaso takes from this tradition we will underscore one, already present in Vasari but differently seen by Palomino: the character of the artist, which in Palomino seems closer to eighteenth-century sociability than to the extravagance of the melancholic genius.
Keywords: Antonio de Palomino; biography; El Parnaso español pintoresco laureado; rhetorical tradition.